Biodegradation of chlorobenzene and chlorophenols by pseudomonas cultures - Bhaskar, Gaikwad G.; Rita, Varma J. (Research Journal of Chemistry and Environment, 2013)
Cultures from NCIM culture collection (National Chemical Laboratory, Pune, India) were screened for biodegradation chlorobenzene (CB). A strain, Pseudomonas sp. NCIM 2303, was found to be most effective. The biodegradation was carried out in aqueous solution by resting cells. The decomposition of 0.02% CB was 96.64% in 24h. We have screened cultures for biodegradation of o-chlorophenol and p-chlorophenol. Pseudomonas sp. NCIM 2668 has shown 94.59% degradation of 0.15% o-chlorophenol. Pseudomonas sp. NCIM 2668 has shown 31.42% degradation of 0.2% p-chlorophenol.
Keywords: Biodegradation; chloride; chlorobenzene; etc.; pollution; Pseudomonas sp

Possible mechanism of antifungal phenazine-1-carboxamide from pseudomonas sp against dimorphic fungi Benjaminiella poitrasii and human pathogen Candida albicans - Tupe, S. G.; Kulkarni, R. R.; Shirazi, F.; Sant, D. G.; Joshi, Swati P.; Deshpande, Mukund V. (Journal of Applied Microbiology, 2015)
AimInvestigation of antifungal mechanism of phenazine 1-carboxamide (PC) produced by a Pseudomonas strain MCC2142. Methods and ResultsAn antifungal metabolite produced by a Pseudomonas was purified and identified as PC. Human pathogenic fungi such as Candida albicans, Candidaglabrata, Cryptococcus neoformans, Fusarium oxysporum, Aspergillus fumigatus and Aspergillus niger were found to be inhibited by PC (MIC90 32-64gml(-1)). Addition of PC (20gml(-1)) during yeast (Y)-hypha (H) transitions inhibited germ tube formation by >90% and >99% in C.albicans National Collection of Industrial Microorganisms (NCIM) 3471 and nonpathogenic model Benjaminiella poitrasii, respectively. After exposure to PC (20gml(-1)), 75-80% yeast cells of B.poitrasii and C.albicans NCIM 3471 showed rhodamine 123 fluorescence indicating high intracellular reactive oxygen species (ROS) production. ROS further led to hyperpolarization of mitochondrial membrane, subsequently induction of apoptosis as evident by externalization of phosphatidylserine, DNA fragmentation, chromatin condensation and finally death in B.poitrasii. In C.albicans NCIM 3471, PC (20gml(-1)) induced apoptosis. ConclusionsThe antifungal effect of PC in B.poitrasii and C.albicans may be due to ROS-mediated apoptotic death. Significance and Impact of the StudyInhibition of Y-H transition of B.poitrasii and C.albicans by PC indicates that it may prove useful in the control of dimorphic human pathogens.
Keywords: Apoptosis; Candida albicans; dimorphism; phenazines; Pseudomonas sp; reactive oxygen species